Business Plan Development Guide - Swanson, Lee; Open Textbook Library (Open Textbook Library, 2017)
This textbook and its accompanying spreadsheet templates were designed with and for students wanting a practical and easy-to-follow guide for developing a business plan. It follows a unique format that both explains what to do and demonstrates how to do it.
Introduction -- Chapter 1 - Developing a Business Plan -- Chapter 2 - Essential Initial Research -- Chapter 3 - Business Models -- Chapter 4 - Initial Business Plan Draft -- Chapter 5 - Making the Business Plan Realistic -- Chapter 6 - Making the Plan Appeal to Stakeholders and Desirable to the Entrepreneur -- Chapter 7 - Finishing the Business Plan -- Chapter 8 - Business Plan Pitches -- ReferencesAppendix A - Business Plan Development Checklist and Project PlannerAppendix B - Fashion Importers Inc. Business PlanBusiness Plan Excel Template
In English.
Description based on print resource
Keywords: Business -- Textbooks; Management -- Textbooks